A pilot investigation among secondary school children into the energy cost of activities traditionally considered sedentary - Dockrell, Sara; Forde, Cuisle; Walsh, C.; O'Sullivan, M.; O'Brien, C.; Gormley, John; Dockrell, Sara (My University, 2015)
The growing trend in increased sedentary behaviour (SB) and decreased physical activity (PA) levels is of concern worldwide (Gordon-Larsen et al, 2004). It is currently suggested that SB is a distinct, independent risk factor for mortality (Koster et al, 2012) and is increasingly linked with adverse health outcomes in both adults and children (Tremblay et al, 2011). SB is defined as ‘any waking behaviour characterised by an energy expenditure of ≤1.5 metabolic equivalents (METs) while in a sitting or reclining posture‘ (Sedentary Behaviour Research Network, 2012). However, the evidence supporting the accuracy of MET values for SB in the adolescent population remains sparse.
ISCP Annual Conference
Keywords: Sedentary behaviour; Physical activity levels; Adolescent; Ergonomics; Ergonomics in Schools; PHYSICAL ACTIVITY; Sedentary behaviour